Border Adjustments on Energy Taxes: A Possible Tool for European Policymakers in Implementing the Kyoto Protocol? - Frank Biermann; Rainer Brohm (Vierteljahrshefte zur Wirtschaftsforschung, 2005)
This article analyses whether the European Union could lawfully enact border adjustments for energy taxes vis-à-vis other industrialised countries that are not party to the 1997 Kyoto Protocol to the UN Framework Convention on Climate Change without violating world trade law, in particular the General Agreement on Tariffs and Trade (GATT) and the Agreement on Subsidies and Countervailing Measures (SCM Agreement). We outline the rationale for border adjustments for energy taxes and conclude that despite remaining ambiguity in both the legal provisions and the pertinent case law, energy-related border tax adjustments are under certain circumstances compatible with world trade law. – – In diesem Artikel wird untersucht, ob die Europäische Union bestehende und künftig drohende Wettbewerbsnachteile infolge nationaler Energiesteuern mit Hilfe von Grenzausgleichssteuern (Border Tax Adjustments, BTA) gegenüber Nichtunterstützerstaaten des Kyoto-Protokolls von 1997 neutralisieren kann, ohne in Konflikt mit dem geltenden Welthandelsrecht zu geraten, insbesondere mit dem Allgemeinen Zoll- und Handelsabkommen (General Agreement on Tariffs and Trade, GATT) und dem Subventionsabkommen (Agreement on Subsidies and Countervailing Measures, SCM Agreement). Unsere Analyse kommt zu dem Ergebnis, dass trotz verbleibender Unklarheiten im Vertragsrecht und der Rechtsprechung der Grenzausgleich von Energiesteuern unter bestimmten Voraussetzungen im Einklang mit dem Welthandelsrecht steht.
Keywords: 330; Internationales Umweltrecht; Energiesteuer; WTO-Recht; Umweltabkommen; EU-Staaten